Quality of life among patients with age-related severe macular degeneration assessed using the NEI-VFQ, HADS-A, HADS-D and SF-36 tests. A cross-sectional study - Inan,Sibel (2019)
ABSTRACT BACKGROUND: Exudative age-related macular degeneration (e-AMD) may cause severe central vision loss. Patients with e-AMD can experience difficulties in daily basic activities and suffer from psychological problems. Our aim was to assess quality of life (QoL) and anxiety and depression status among patients with e-AMD. DESIGN AND SETTING: Cross-sectional study in a state university. METHODS: We included 200 e-AMD patients and 120 age and gender-matched controls. We assessed QoL using the National Eye Institute Visual Functioning Questionnaire-25 (NEI-VFQ-25) and the Short Form (SF)-36 test; and anxiety and depression status using the Hospital Anxiety Depression Scales A and D (HADS-A and HADS-D). RESULTS: The mean ages in the e-AMD and control groups were 68.40 ± 9.8 and 66.31 ± 8.98, respectively. Visual acuity among e-AMD patients was 0.37 ± 0.31 and 0.39 ± 0.32 in the right and left eyes, respectively. The e-AMD patients performed significantly worse than the controls in NEI-VFQ-25 (P < 0.05 for all items). The proportions of e-AMD patients scoring higher than the cutoffs in HADS-A and HADS-D were significantly higher than among the controls (41.5% versus 12.5% and 63.5% versus 27.5%; P < 0.001). The e-AMD patients had significantly lower mean scores than the controls for each of the SF-36 QoL items (P < 0.001). The NEI-VFQ-25 scores were significantly lower among patients with bilateral e-AMD than among those with unilateral disease (P < 0.05 for all). The HADS scores were positively correlated with duration of e-AMD and patient age, but negatively with vision levels (P < 0.05 for all items). CONCLUSION: The e-AMD patients had higher depression and anxiety scores and lower QoL scores.